If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.20x + 3y + 3 = 2x + -14y Reorder the terms: 3 + 0.20x + 3y = 2x + -14y Solving 3 + 0.20x + 3y = 2x + -14y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3 + 0.20x + -2x + 3y = 2x + -2x + -14y Combine like terms: 0.20x + -2x = -1.8x 3 + -1.8x + 3y = 2x + -2x + -14y Combine like terms: 2x + -2x = 0 3 + -1.8x + 3y = 0 + -14y 3 + -1.8x + 3y = -14y Add '-3' to each side of the equation. 3 + -1.8x + -3 + 3y = -3 + -14y Reorder the terms: 3 + -3 + -1.8x + 3y = -3 + -14y Combine like terms: 3 + -3 = 0 0 + -1.8x + 3y = -3 + -14y -1.8x + 3y = -3 + -14y Add '-3y' to each side of the equation. -1.8x + 3y + -3y = -3 + -14y + -3y Combine like terms: 3y + -3y = 0 -1.8x + 0 = -3 + -14y + -3y -1.8x = -3 + -14y + -3y Combine like terms: -14y + -3y = -17y -1.8x = -3 + -17y Divide each side by '-1.8'. x = 1.666666667 + 9.444444444y Simplifying x = 1.666666667 + 9.444444444y
| 14x-(5x+6)+16=4x | | 9-4x=17+4x | | 7x+9=9x+7 | | b=8m+9 | | 8x=26+14y | | 18-2x+x=6x-3 | | 90+45w=960 | | -132+2x=-6x+44 | | (x+2)-4=-3x+12 | | 4w+7x-13y+5w+5x+7y= | | 4y-2(4)=16 | | 42=14y-7y | | -132+2x=10x+50 | | 5+x+3x=4x+5 | | (2x^2+11x-18)=0 | | -6x-78=57-x | | 10=6y+2+3y+17 | | 4+3+2+6+10= | | 4(x-1)=5.6 | | 2(m-22)+3(m-4)=36 | | 1.4(5x-0.2)= | | x+-39=-2x+33 | | 25(2x^2+11x-18)=0 | | z-39=-2x+33 | | 40-5w=3w | | 2e-5=-4.6 | | 5x+(-x)= | | 3n-7n+12=32 | | 6z=16 | | 19.8x=91 | | 50x^2+275x-450=0 | | -51+6x=84+11x |